O Novo profissional da rede estadual do Rio Grande do Sul e as tecnologias na educação - Patrícia B. Scherer Bassani; Dinora Tereza Zuchetti; Mely Paula Rabadan Cimadevila (Universidade Estadual de Campinas, 2013)
Education in the Information Society is not just about training for the use of information and communication technologies (ICT), but involves the development of skills that allow the subject to engage effectively in a society permeated by digital technologies. It is understood that experiencing new forms of teaching and learning mediated by ICT refers to a (re)thinking about the processes of teacher training. Method: The research The new professional of education in the public schools of the state of Rio Grande do Sul (RS) and the technologies in education was conducted in two stages: first, quantitative, was responsible for the characterization of the professional who were hired between the years 2008 to 2010. The second, qualitative, involved the study of the use of technology in the teacher's activity, from the methodology of self-confrontation. Results: It was possible to draw a profile of the professionals of public education especially in relation to their entrance in the public service as well as the technological appropriation of teachers hired to work in a school in Porto Alegre. The article highlights the relevance of the methodology of self-confrontation as a space for teacher training in relation to technology in education. Conclusions: The technological appropriation is not due to existing training undergraduate and is not coming from the in-service training, although the government provides this type of qualification by the state policy of digital inclusion. Are the experiences of daily life that give the support for the work in this type of activity.